Activation of antioxidant enzymes as a mechanism against cadmium stress in Mimosa scabrella - Wertonge, Gerâne Silva; Aguilar, Marcos Vinícius Miranda; Senhor, Daiane Franchesca; Kuinchtner, Caroline Castro; Rorato, Daniele Guarienti; Tabaldi, Luciane Almeri (Revista em Agronegócio e Meio Ambiente, 2024)
Among the elements that cause serious consequences to the environment and to living beings, cadmium (Cd) is considered one of the most harmful. When reaching high levels of Cd contamination in an area, vegetation suppression can occur. Thus, the objective was to analyze the effects of Cd on morphological and biochemical variables of Mimosa scabrella, in order to evaluate its potential for use in environments polluted by Cd. M. scabrella seedlings were grown in five concentrations of Cd (0, 25, 50, 75 and 100 µM). The morphological variables of leaves and roots, photosynthetic pigments, antioxidant enzyme activity, as well as the content of hydrogen peroxide and lipid peroxidation (MDA) were evaluated. No negative effects were observed on the total length and surface area of roots at concentrations lower than 75 µM Cd. Cd stress activated enzymatic antioxidants, mainly in roots of M. scabrella seedlings, thus causing maintenance in the production of biomass of roots and shoot of seedlings. Thus, the species tolerated high concentrations of Cd and could be recommended for phytoremediation of soils contaminated with cadmium.